The Contribution of Digital Marketing to Tourist Visit Intention through Destination Image Mediation: Creative Tourism Perspective - I Kadek Daniel Surya Nadi; Ni Nyoman Sri Wisudawati; Putu Ratna Juwita Sari; Anak Agung Istri Agung Maheswari (Journal of Innovative and Creativity, 2025)
Creative tourism has increasingly shifted the tourism value from passive sightseeing into participatory cultural experience, strengthening emotional destination attachment and revisitation intention. However, seasonal fluctuation and global tourism competition continue to challenge visitor stability in Bali, particularly in artistic hubs including Ubud, Celuk, Mas, and Batuan, Gianyar Regency. This examines how digital marketing influences tourist’s intention to visit, while positioning destination image as the intermediary factor, viewed through a creative tourism context and Destination Branding Theory. A quantitative method was applied using survey-based data and variance-using a Structural Equation Modeling approach (SEM-PLS). The study population consists of potential and past tourists interested in creative tourism activities such as silver crafting, wood carving, traditional painting, and cultural workshops. Indicators of digital marketing include social media utilization, search engine optimization, email marketing exposure, and Google business visibility. Destination image is measured through cognitive, affective, and uniqueness dimensions, while visit intention is assessed via attraction appeal, accessibility, amenity, and revisit interest. Findings from previous empirical benchmarks confirm that digital marketing significantly improves destination image, which in turn drives visit intention. However, contradictory evidence suggests that digital exposure does not always directly increase visit intention without a strong destination identity and experiential value. This study fills the gap by positioning destination image as the key mediator, specifically within creative tourism attributes emphasizing co-creation experiences, authenticity, and interactive cultural engagement. The study contributes theoretically to Destination Branding Theory expansion and practically as a digital marketing strategy framework for creative tourism destinations in Bali.